SUBJECT-PEDAGOGIC ICT-COMPETENCE FOR TEACHERS OF FOREIGN LANGUAGE - Natalia B. Romaeva; Marina N. Degtyareva (Вестник Северо-Кавказского федерального университета)
The article offers a theoretical rationale for the practical implementation of the model for developing subject-pedagogic ICT-competence in foreign language teachers given the context of the professional standard “PEDAGOGUE” and the Federal State Educational Standard for general education (example of Stavropol region).